Pistols for two, and other stories - Heyer, Georgette (Naperville, Ill. : Sourcebooks Casablanca, 2012)
"In eleven charming short stories, the Queen of Regency romance presents an exquisite romp through affairs of honor and affairs of the heart. Featuring rakes and rascals, orphans and heirs, beauties and their beaus, the legendary Georgette Heyer's signature wit and immitable style bring the regency world dazzlingly alive."--P. [4] of cover.
Pistols for two -- A clandestine affair -- Bath miss -- Pink domino -- A husband for Fanny -- To have the honour -- Night at the inn -- The duel -- Hazard -- Snowdrift -- Full moon.
"Originally published in the United Kingdom in 1960 by William Heinemann"--Tp verso.
Keywords: England -- Social life and customs -- 19th century